(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Inclusive Education (IE) is a step forward in re-affirming the rights of all children to be given equal opportunities and to be treated with respect. It means that schools and classrooms must function assuming that students with special needs are also competent just like any other student. One important element that ensures this right is providing teachers who not only believe in the philosophy of IE but also has the skill set to cater to students with special needs. The present study was attempted with aimed to assess teachers’ attitudes towards IE among those who had courses on IE as opposed to those teacher-trainees who did not study any IE course. Results indicated that overall, teacher-trainees who had IE course are likely to have more favorable attitude towards IE as compared to teacher-trainees who did not have any IE course. On the components, no significant differences were observed between the two groups on issues of IE philosophy and logistical concerns indicating. The two groups however differed significantly on advantages and limitations of IE and issues related to professional requirements. The study highlights the need of having a compulsory course of IE for pre-service teachers.